ORAL WHITE LESIONS - HISTOMORHOLOGICAL ASSESSMENT AND ASSOCIATED RISK FACTORS - Orakzai, Gulmina Saeed; Nisa, Waqar Un; Orakzai, Saima Hanif (Journal of Ayub Medical College Abbottabad, 2015)
Background: Oral white lesions constitute a major clinical problem in Pakistan and South Asian countries. The study was done with the objective to analyse oral white lesions histologically and clinically, and evaluate association between various risk factors in different ages, gender, ethnic groups, sites and sizes of the lesion. Methods: A total of 80 patients presenting with oral white lesions were included in this cross-sectional study conducted at Department of Histopathology, Armed Forces Institute of Pathology (AFIP), Rawalpindi. The biopsy sample was fixed in 10% formalin and after standardized processing, slides were prepared, stained by Hematoxylin and Eosin, with special stains when required. The histo-pathological diagnosis of lesion was recorded. Mean and standard deviation were calculated for quantitative variable. Frequency and percentages were calculated for qualitative variables. Results: Out of total 80 patients 43 were females and 37 males. The mean age of cases was 47.92 years. Majority of the patients were between 30-39 years. Buccal mucosa was affected in majority of the cases (55%), followed by lateral border of tongue 17.5% and lip mucosa (8.8%). No risk factor had been observed in almost half of the patients. Histologically Lichen Planus was the most common lesion (32.5%), followed by chronic nonspecific inflammation in (22.5%), keratosis without dysplasia (10%), keratosis with dysplasia (8.8%), Pemphigus vulgaris (7.5%), fungal infestation (5%) and Squamous cell carcinoma (3.8%). Conclusion: Oral Lichen Planus was the most common oral white lesion in our set up, with buccal mucosa involved in majority of the cases. Association between histo-pathological diagnosis with age and gender was insignificant. However, significant association was observed between histopathological diagnosis and site. Among risk factors significant association was seen between snuff dippers and pan users.